GENESIS OF AN AMERICAN SUPERPOWER - Browne, Blaine T. (Blaine Terry) Link ([S.l.])
1 online resource
Keywords: This book is the first comprehensive analysis of a crucial transitional period in American history, when the nation abandoned its previous isolationist tradition and accepted the burdens of global leadership in the aftermath of World War II.American society, culture, economy and politics were all transformed in the postwar era, as an abundant society evolved and confronted crucial issues such as coping with the nuclear age and addressing civil rights. During the presidency of Harry Truman, the United States undertook the reconstruction of Europe, the occupation of Germany and Japan, participated in the judicial prosecution of war criminals and instituted the policies and agencies necessary to confront the expansion of Soviet power as the Cold War took shape. The structure of a modern national security state began to form as the military was reorganized to accommodate the possible use of nuclear weapons and combat newly arisen threats. Alongside analyzing the historical, political and economic developments that led to America's dramatic transformation, each chapter also sheds light on key figures of the era including Eleanor Roosevelt, Humphrey Bogart and Bayard Rustin.The Genesis of an American Superpower is a unique resource aimed at general readers and undergraduates, graduates and scholars alike interested in modern American history and politics.